Effect of manganese sulphide particle shape on the pinning of grain boundary. Issue 8 (24th May 2017) - Guo, L.; Roelofs, H.; Lembke, M. I.; Bhadeshia, H. K. D. H.
Abstract : The pinning of austenite grain boundaries by manganese sulphide particles is examined experimentally as a function of the shape and size of the inclusions in a free-machining steel. With the same volume fraction, large and extremely long MnS particles are found to be more effective at hindering the motion of austenite grain boundaries than those that approximate spherical shape, even when the latter are smaller and have a higher number density.